Track squad, 1913 - Munro, Melville S. (Tufts Archival Research Center, 2005)
5x7; (left to right) Lawrence Howes Teel, James Henry Holden, Everett Austin Geer, Roland Grover Stafford or Henry Alexander Stafford, Robert Leston McLellan; Munro Scrapbook: Vol. 1, Box No. 1, Pg. 10